ANALISIS KEBUTUHAN TENTANG NILAI-NILAI KEBHINEKAAN DALAM PENDIDIKAN MULTIKULTURAL (Studi Pada Para Siswa SMP Yayasan Insan Mandiri se Bali) - Lestari, Ana Endang (Jurnal Penelitian dan Evaluasi Pendidikan Indonesia, 2012)
ABSTRAK   Penelitian ini bertujuan untuk mengetahui tentang nilai-nilai kebhinekaan yang paling dibutuhkan dalam mengembangkan pendidikan multikultural pada siswa SMP di Yayasan Insan Mandiri. Populasi dalam penelitian ini adalah siswa dan guru yang terdapat di empat lokasi yaitu (1) SMP St. Yoseph-Denpasar (2) SMP St. Paulus-Singaraja, (3) SMP. St. Thomas Aquino-Padang Tawang, (4) SMP Wana Murni ? Palasari. Jumlah siswa keseluruhan 1464 orang, jumlah guru 73 orang. Sampel pada penelitian ini menggunakan teknik purposive sampling dengan penentuan jumlah sampel menggunakan tabel Isaac & Michael dengan taraf kesalahan 5%. Penelitian ini dirancang  dengan metode Penelitian dan  Pengembangan tahap dasar. Data dalam penelitian ini dikumpulkan dengan menggunakan kuesioner  yakni nilai-nilai kebhinekaan : (1) Religiositas, dengan perolehan persentil mean 76,52 dan 54,77, (2) Kemandirian Moral, dengan perolehan persentil mean 76,75 dan 77,35, (3) Kesediaan untuk bertanggung jawab, dengan perolehan persentil mean 75,88 dan 79,56, (4) Nasionalisme, dengan perolehan persentil mean 81,8 dan 74,56, (5) Demokrasi, dengan perolehan persentil mean 73,31 dan 76,18, (6) Kepedulian sosial, dengan perolehan persentil mean 71,54 dan 85,23. Untuk pengembangan kurikulum dalam pendidikan multikultural dengan perolehan persentil mean 73,64. Statistik yang dipergunakan untuk menganalisis data adalah dengan menggunakan ukuran univariat yakni penelitian deskriptif kuantitatif. Dengan rentangan persentil yang menggunakan klasifikasi dari Delphi, hasil penelitian menunjukkan bahwa: (1) nilai-nilai kebhinekaan yang dibutuhkan oleh siswa SMP dalam lingkungan Yayasan Insan Mandiri adalah nilai Nasionalisme, nilai Demokrasi dan nilai Kepedulian sosial. (2) Pengembangan kurikulum dalam pendidikan multikultural adalah mengintegrasikan penanaman nilai-nilai kebhinekaan dalam pelajaran-pelajaran dengan berangkat dari situasi konkrit  hidup para siswa serta dibarengi teladan sikap dari para pendidik. Kata kunci: Nilai-nilai Kebhinekaan, Pendidikan Multikultural, Siswa SMP.   ABSTRACT The aim of the study is to explore multicultural values needed in order to develop a so-called multicultural educational curriculum for the junior high schools belong to Yayasan Insan Mandiri. The respondents selected for the study composed of  both the junior high school students and their teachers from: 1) St.Yoseph Junior High School in Denpasar; 2) St. Paul Junior High School in Singaraja; 3) St. Thomas Aquinas Junior High School in Padang Tawang; and 4) Wana Murni Junior High School in Palasari. The total students taken for study were 1464, and the teachers were 74. Those respondents selected by applying purposive sampling technique as proposed by Isaac & Michael. The standard of error of sampling process is about 5 %. The research was designed by using a very basic research and development method. The data on the multicultural values particularly connected to religiosity, morality, responsibility, nationalism, democracy, and social responsibility collected by questionnaire technique. The results of data analysis discovered that the students in general have a positive attitude toward multicultural values. Such attitude demonstrated by: 1) the percentile mean of religiosity was 76,75 and 77,35; 2) the percentile mean of  moral independency attitude was 76,75 and 76,53; 3) the percentile mean of personal responsibility was about 75,88 and 79,56; 4) the percentile mean of nationalism was 81,8 and 74,56; 5) the percentile mean of  nationalism was 81,8 and 74,56; 5) the percentile mean of democracy was 73,31 and 76,18; and 6) the percentile mean of social responsibility was 71,54 and 85,23. However, the percentile mean of developing a curriculum for multicultural education was 73, 64. The model of statistics used to analyze such data is univariat or descriptive-quantitative model. Percentile data analysis based on Delphi?s classification reflected the results of study as following: (1) the pluralistic values are needed by the junior high school students who are studying at the junior high schools belong to Yayasan Insan Mandiri. The pluralistic values are including nationalism, democratic and the social responsibility values. (2) The effort to develop junior high school?s multicultural curriculum should be based on practical efforts and experiences of the school community in promoting multicultural values throughout its social and personal relationship and teaching process in the school.   The key words: Multicultural values, multicultural education, junior high school.